Optimizing Academic Data Integrity through the Design of an Integrated Relational Database with Normalization - Syahruni Runi; Fitri Yunita; Endy Sudeska (Jurnal Armada Informatika, 2026)
anual academic data management often leads to data redundancy, information inconsistency, and obstacles in data reporting within educational institutions. This study aims to design an Academic Management System (AMS) database capable of integrating student, teacher, schedule, and administrative data into a single, structured system. The method employed is the Database Development Life Cycle (DDLC), which includes requirements analysis, Entity Relationship Diagram (ERD) modeling, and the application of normalization to maintain data integrity using the MariaDB DBMS. The results demonstrate that the designed database structure successfully minimizes data redundancy and improves information storage efficiency. The study concludes that the application of normalization in a relational database significantly enhances the performance of academic data